A new perspective on the size, value, and momentum effects: Broad sample evidence from Europe. Issue 2 (9th May 2016) - Foye, James
Abstract : Purpose: This paper aims to provide a comprehensive analysis of whether stock returns in Europe are best characterized by country-specific or Europe-wide versions of widely used factor models. Design/methodology/approach: To estimate the cost of equity in Europe, both region-wide and nationally, the Fama and French (2012) three-factor and Carhart (1997) four-factor models are used. Findings: The results show that although the value and momentum premiums are present on a Europe-wide basis, the size premium is country-specific. Originality/value: The paper offers an explanation to the puzzle of why Fama and French (2012) detect value and momentum premiums but no size premium in Europe. Furthermore, the results shed new light on these premiums and present a challenge to existing applications of widely used factor models.